Measurement of Bed Turning and Comparison with Age, Gender, and Body Mass Index in a Healthy Population: Application of a Novel Mobility Detection System. (29th April 2014) - Chiang, Shang-Lin; Lin, Chia-Huei; Chang, Shin-Tsu; Lin, Chueh-Ho; Chen, Po-Yin; Sung, Wen-Hsu; Wei, Shun-Hwa
Abstract : We developed a mobility detection system to analyze pressure changes over time during side-turns in 29 healthy volunteers (17 males and 12 females) with a mean age of 46.1 ± 19.64 years (ranging from 23 to 86 years) in order to determine the effect of gender, age, and BMI on performance during bed postural change. Center of gravity (COG) location, peak pressure of counteraction, and time to reach peak pressure were the main outcomes used to gauge the ability to make a spontaneous side-turn. Men exhibited significantly higher side-turning force (P = 0.002 ) and back-turning force (P = 0.002 ) compared with women. Subjects with BMI ≥27 kg/m 2 had significantly higher side-turning force (P = 0.007 ) and back-turning force (P = 0.007 ) compared with those with BMI < 27 kg/m 2 . After adjusting for other covariates, age positively correlated with back-turning time (P = 0.033 ) and negatively correlated with side-turning speed (P = 0.005 ), back-turning speed (P = 0.014 ), side-turning force (P = 0.010 ), and back-turning force (P = 0.016 ), respectively. Turning times negatively correlated with time to reach peak pressure (P = 0.008 ). Our system was effective in detecting changes in turning swiftness in the bed-ridden subject.